The transcriptional landscape of the clustered protocadherins in the cardiovascular system. (14th October 2021) - Zhu, W; Chhibbar, P; Lo, C
Abstract: Background: The alpha, beta and gamma clustered protocadherins (cPcdhs) genes encode homotypic cell adhesion molecules that are highly expressed in the brain. They are well described to be expressed in a combinatorial fashion to specify neuronal identity for coding synaptic connectivity. Unexpectedly, we recently uncovered evidence from studies in mice and human showing PCHDA variants can cause congenital heart defects. As all the genes of the alpha or gamma PCDH cluster share a common 3' end and are highly homologous, the expression of these gene clusters has been underestimated or overlooked due to multimapping issues. This is especially problematic in single cell RNAseq (scRNA) data generated using 3' based amplification protocols. Methods and results: We constructed a modified bioinformatic pipeline for analyzing the cPcdhs transcripts (Fig. 1a). Raw data of Publicly available scRNA datasets were downloaded and re-processed and analyzed for expression of the cPCDH transcripts using our custom pipeline. Integrating 10 scRNA datasets of mouse heart tissues from embryonic 7.75 (E7.75) to postnatal 30 months (PM30) were performed by Harmony and Seurat. This showed Pcdhg had the highest expression among the three Pcdh gene clusters, with next being Pcdhb and then Pcdha (Fig. 1b). Pcdhb and Pcdhg were enriched in endocardial cells and fibroblasts (Fig. 1b). Unlike gene expression in neurons, expression of the cPcdhs in cardiac cell types did not shown the stochastic, sparse, combinatorial expression patterns seen in neurons (Fig. 1b). Despite the relatively low level of Pcdha expression in all cardiac cell types, it is intriguing that independent scRNA datasets showed Pcdha is expressed most highly in the atrium in the early embryo, possibly due to known atrial dominance in the early embryo (Fig. 1c). Pcdhb is highly expressed in the OFT and atrioventricular canal of both human and mouse heart, suggesting its perturbation may contribute to outflow tract or AV valve abnormalities (Fig. 1c-d). Consistent with our previous finding of an important role for the Pcdha gene cluster in left ventricular outflow obstructive (LVOTO) lesions, we observed expression of Pcdhg was broadly upregulated in the Adamts19 homozygous knockout mice exhibiting aortic valve dysfunction, a CHD phenotype in the LVOTO spectrum (Fig. 1e). Conclusions: Using a new bioinformatics pipeline, we systematically mapped the transcriptional landscapes of cPcdhs during heart development using scRNA data. This revealed cell type-specific and anatomical characteristics in the expression of the different cPcdhs. These findings show the cPcdhs are transcriptionally regulated very differently in the cardiovascular system from regulation observed in the brain. The single cell transcriptional profile for the cPcdhs in the cardiovascular system can serve as the foundation for future investigations into the broader role of the cPcdhs in cardiovascular development and disease. Funding Acknowledgement: Type of funding sources: None.